PKM2 Interacts With the Cdk1-CyclinB Complex to Facilitate Cell Cycle Progression in Gliomas - Ohba, Shigeo; Tang, Yongjian; Johannessen, Tor-Christian Aase; Mukherjee, Joydeep (Frontiers in Oncology, 2022)
PKM2 is a phosphotyrosine-binding glycolytic enzyme that is up regulated in many cancers including glioma and contributes to tumor growth by regulating cell cycle progression. We noted, however, that in multiple glioma cell lines, PKM2 knockdown resulted in an accumulation of cells in G2-M phase. Moreover, PKM2 knockdown decreased Cdk1 activity while introduction of a constitutively active Cdk1 reversed the effects of PKM2 knockdown on cell cycle progression. The means by which PKM2 increases Cdk1 activity have not been described. Transient interaction of T14/Y15-phosphorylated Cdk1 with cyclin B allows Cdk7-mediated pT161 Cdk1 phosphorylation followed by cdc25C-mediated removal of pT14/Y15 and activation of Cdk1 in cycling cells. In the present course of investigation PKM2 modulation did not influence Cdk7 activity but phosphotyrosine binding forms of PKM2 co-immunoprecipitated with pY15-containing Cdk1-cyclinB and enhanced formation of active pT161 Cdk1-cyclin B complexes. Moreover, exogenous expression of phosphotyrosine binding forms of PKM2 reversed the effects of PKM2 knockdown on G2-M arrest. We here show that PKM2 bind and stabilize otherwise transient pY15-containing Cdk1-cyclinB complexes that in turn facilitates Cdk1-cyclin B activation and entry of cells into mitosis. These results therefore establish metabolic enzyme PKM2 as a direct interactor and activator of Cdk1-cyclin B complex and thereby directly controls mitotic progression and the growth of brain tumor cells.